The Role of Media in Purchase Intention for Eco-Labelled Products with Advertising Value and Attitude as Mediator - Edy Yulianto Putra; Erlin Erlin (International Journal of Economics Development Research (IJEDR), 2024)
The Era of Globalization allows the general public to know information and communication technology quickly. One of the information received by the community is environmental problems. This is what makes people aware that environmental damage occurs as a result of the products used can increase the accumulation of waste. As for technological developments that are getting higher in encouraging business people to innovate. Therefore, the purpose of this study is to analyze the influence of entertainment, informativeness, and irritation in determining customer purchase intentions for eco-labeled products mediated by attitude and advertising value. This research method is a quantitative method with a purposive sampling technique. The population in this study is social media users in Batam. The number of respondents in this study was 260 and it had 26 questions. The analysis used in this research is PLS-SEM.